Analysis of inrush currents of the unloaded transformer using the circuitfield modelling methods - Yarymbash, Dmytro; Yarymbash, Serhiy; Kotsur, Mykhailo; Divchuk, Tetyana (Eastern-European Journal of Enterprise Technologies, 2018)
We studied theoretically the transition processes that occur during tests of power transformers in the mode of experimental idling. A circuit-field model of electromagnetic processes is developed, based on a three-dimensional dynamical model of the magnetic field in a three-phase power transformer at idling. Using a finite element method, we divided the region of field simulation into estimated zones with the magnetic field symmetry conditions for vertical and horizontal cross sections. The number of finite elements and the time for computing was reduced by four times without compromising the accuracy of our results. It was established that in the circuit of the windings, connected into a triangle, there occurs a transitional levelling current, which fades over the initial switching time. The multiplicity of this current may reach 60‒70 % of the multiplicity of the input surge current. We have developed relations for the approximation of transitional phase currents, which are represented by the aperiodic, periodic components and series with the basis Gaussian functions for phase current discrepancies between the circuit-field and circuit models. We have proposed and implemented a refined approach for the calculation of input surge current based on the specifications for an idling mode of the transformer and a surge current coefficient, which is characterized by the high efficiency and accuracy of numerical realization. To determine a functional dependence of the multiplicity coefficient for an input surge current on the input resistances, we applied a method of sorting out specialized functions. The approximation coefficients calculation was carried out based on the method of least squares. This allowed us to significantly reduce the level of error when calculating the multiplicity coefficient of input surge current based on the specifications of the transformer and testing equipment, by 2.1 %. Using the 3D modeling reduces the calculation error of idling mode current surges by 2.4 % using a simplified procedure that employs specifications of the transformer.